MANAGEMENT OF MADURA CATTLE FEED IN WARU TIMUR VILLAGE, PAMEKASAN REGENCY: MANAGEMENT OF MADURA CATTLE FEED IN WARU TIMUR VILLAGE, PAMEKASAN REGENCY - Kurnia, Faridatul; diyah, Mardiyah Hayati; Rum, Mokh; Triyasari, Sri Ratna (Jurnal Peternakan Nusantara, 2023)
Feed is one important factor in livestock. The problem experienced by Madura cattle breeders is limited feed, especially during the dry season which results in unfulfilled cattle feed needs. The purpose of this study was to identify the types of animal feed in Lembanah Hamlet to find out the pattern of feed management in Lembanah Hamlet. This research was conducted in Lembanah Hamlet, Waru Timur Village. The respondents used were the Bringin Jaya farmer group. The research analysis method used is descriptive qualitative analysis with triangulation techniques. The results showed that the types of feed identified were weeds, agricultural waste and plant leaves. Farmers experience a shortage of feed during the dry season, this is due to a lack of feed availability. Management of feeding has not been implemented properly. Breeders still lack knowledge about good and correct management of Madura cattle feeding. There needs to be counseling to support breeders' knowledge regarding developing technologies such as feed fermentation. This innovation is very beneficial for farmers who experience a shortage of feed